2017
DOI: 10.21061/jcte.v31i1.1506
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Community College Outcomes: Does High School CTE Participation Have a Significant Effect?

Abstract: The Role of Academic Student Services in the Retention of American Indian Students at a Sub-Baccalaureate Technical College.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(45 reference statements)
1
2
0
Order By: Relevance
“…Studies of CTE coursetaking have consistently found an association between a CTE focus and 2-yearcollege enrollment and success (Dougherty, 2016;Dietrich, Lichtenberger & Kamalludeen, 2016;Phelps & Chan, 2016). Similar to CTE coursetaking, we found a positive association between earning certifications and immediate postsecondary enrollment at 2-year programs.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Studies of CTE coursetaking have consistently found an association between a CTE focus and 2-yearcollege enrollment and success (Dougherty, 2016;Dietrich, Lichtenberger & Kamalludeen, 2016;Phelps & Chan, 2016). Similar to CTE coursetaking, we found a positive association between earning certifications and immediate postsecondary enrollment at 2-year programs.…”
Section: Discussionsupporting
confidence: 75%
“…In Arkansas, students who took an additional CTE course had higher high school graduation rates and were more likely to enroll in a community college (Dougherty, 2016). Once in community colleges, students who had participated in a CTE program during high school had higher odds of earning an associate degree than community college students who had taken a general education program (Dietrich, Lichtenberger & Kamalludeen, 2016). In particular, high school students who had taken dual credit CTE courses in high school had higher rates of continued enrollment and degree attainment in community college (Phelps & Chan, 2016).…”
Section: Educational Benefits Of Gaining Job Skills In High Schoolmentioning
confidence: 98%
“…Outcomes Across Student Groups Suggest About Equality of Educational Opportunity in Secondary CTE Much of the research on educational outcomes from our search highlighted practices related to improvements in achievement and attainment but very little on social and emotional outcomes and CTE. For example, studies showed that CTE programs with well-defined career pathways, aligned core academics, and students placed in smaller learning communities (e.g., career academies) had the most positive educational outcomes (Brunner et al, 2019;Advance CTE, 2017;Castellano et al, 2014;Dietrich et al, 2016;Giani, 2017;Gottfried & Plasman, 2017;Kemple & Wilner, 2008;Reed et al, 2018). This was especially true for CTE courses taken later in high school (Gottfried & Plasman, 2017) and when students concentrated in CTE (Dougherty, 2016;Kreisman & Stange, 2017).…”
Section: What Observed Differences In Academic and Social And Emotionalmentioning
confidence: 99%